Controlling autohydrolysis conditions to produce xylan-derived fibers that modulate gut microbiota responses and metabolic outputs - Zhao, Sainan (2022)
Autohydrolysis is used for producing xylan-derived oligosaccharides from lignocellulosic biomass. Although numerous studies report optimized autohydrolysis conditions for various plants, few of these studies correlate process parameters with the resulting structural properties to their impact on intestinal bacterial communities. Thus, to further clarify these relationships, beechwood xylan (BWX)-derived substrates, processed under five conditions, were fermented in vitro by human gut microbiota. Autohydrolysis reduced the mean molecular size and substitutions of BWX. Distinct fermentation kinetics were observed with differing processing of BWX substrates, which correlated with impacts on community species evenness. The relative abundances of Bacteroides, Fusicatenibacter, Bifidobacterium, and Megasphaera within the fermentations varied with processing conditions. While the total short-chain fatty acid concentrations were the same among the treatments, processing conditions varied the extent of propionate and butyrate generation. Autolysis parameters may be an important tool for optimizing beneficial effects of xylan-derived fibers on human gut microbiota structure and function.